Strategi Guru IPS dalam Menumbuhkan Sikap Sosial pada Siswa di MTs Negeri 6 Blitar - Qutrotu Salsabila; Binti Maunah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Social attitudes are activities in relationships with other people, whether with peers, teachers, parents, or siblings. In relationships with other people, very meaningful events occur in his life that shape his personality, which helps him develop into the human being he is. As an educator, cultivating social attitudes in students is very important so that students have the attitude to build relationships with other people in everyday life. Based on this phenomenon, the researcher took research at MTs Negeri 6 Blitar as the object of research with the aim of finding out how social studies teachers' strategies are in cultivating social attitudes in students. The formulation of the problem in this research is: (1) What is the social studies teacher's strategy in determining changes in student behavior and personality at MTs Negeri 6 Blitar? (2) What is the social studies teacher's strategy in cultivating students' social attitudes at MTs Negeri 6 Blitar? (3) What are the results of the social studies teacher's strategy in fostering students' social attitudes at MTs Negeri 6 Blitar? This research uses a descriptive-qualitative approach. The research location is at MTs Negeri 6 Blitar. The data sources in this research use primary and secondary data. Data collection techniques in this research used three techniques, namely, in-depth interviews, observation, and documentation. The data that has been collected is then analyzed through data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that: (1) Implementing behavioral changes at MTs Negeri 6 Blitar starts from class VII students by getting used to: first making a greeting picket schedule after coming to school in the morning, holding the habit of doing dhuha prayers in congregation for all students and teachers, carrying out community service to clean the environment every Friday in mutual cooperation, familiarizing students with literacy, carrying out homeroom clinics to minimize mistakes made by students so that they can be minimized by each homeroom teacher, and teaching students good manners to respect parents, teachers, friends, and other people. Another thing is to get used to reading the Asmaul Husna before starting learning. (2) Developing students' social attitudes at MTs Negeri 6 Blitar by holding a program: they must collect social funds every Friday as sincerely as possible to help less fortunate friends. If they have damaged shoes, they can't afford them; the school buys the shoes using these social funds; treats friends. who are sick while at school; visits friends who are sick; works together to clean the classroom once a week so that students have the social spirit to care about dirty classrooms; picking up rubbish on the floor before starting learning can foster social attitudes by having a sense of caring about the surrounding environment. (3) The results of the teacher's strategy in cultivating students' social attitudes at MTs Negeri 6 Blitar make students more able to appreciate and respect other people, make students have a religious spirit by getting used to praying dhuha in congregation every morning and reading Asmaul Husna before starting social studies learning, make students more caring with the cleanliness of the surrounding environment because of cleaning activities on Fridays, make students love reading by holding literacy, make students more organized and minimize mistakes with the homeroom clinic, and foster a high social spirit with the existence of social funds every Friday and distributing These funds are properly used to buy necessities for underprivileged students, treat friends who are sick while at school, and visit friends who are sick.